Heat and mass transfer fundamentals & applications - Cengel, Yunus A. (McGraw-Hill, 2011)
This text is the recognized standard for learning heat and mass transfer. This text combines detailed coverage with the resources students need to learn the concepts and apply them to solving realistic and relevant problems. Using a rigorous and systematic problem-solving methodology, the text is filled with examples and problems that reveal the richness and beauty of the discipline.